Adiponectin-coated nanoparticles for enhanced imaging of atherosclerotic plaques - Almer G (Dove Medical Press, 2011)
Gunter Almer1,6, Karin Wernig2, Matthias Saba-Lepek3, Samih Haj-Yahya1, Johannes Rattenberger4, Julian Wagner4, Kerstin Gradauer3, Daniela Frascione3, Georg Pabst3, Gerd Leitinger5, Harald Mangge1, Andreas Zimmer2, Ruth Prassl31Clinical Institute of Medical and Chemical Laboratory Diagnostics, 2Institute of Pharmaceutical Sciences, Department of Pharmaceutical Technology, University of Graz, 3Institute of Biophysics and Nanosystems Research, Austrian Academy of Science, 4Institute for Electron Microscopy and Fine Structure Research, Graz University of Technology, 5Institute of Cell Biology, Histology and Embryology, Medical University of Graz, 6Center for Medical Research, Medical University of Graz, AustriaBackground: Atherosclerosis is a leading cause of mortality in the Western world, and plaque diagnosis is still a challenge in cardiovascular medicine. The main focus of this study was to make atherosclerotic plaques visible using targeted nanoparticles for improved imaging. Today various biomarkers are known to be involved in the pathophysiologic scenario of atherosclerotic plaques. One promising new candidate is the globular domain of the adipocytokine adiponectin (gAd), which was used as a targeting sequence in this study.Methods: gAd was coupled to two different types of nanoparticles, namely protamine-oligonucleotide nanoparticles, known as proticles, and sterically stabilized liposomes. Both gAd-targeted nanoparticles were investigated for their potency to characterize critical scenarios within early and advanced atherosclerotic plaque lesions using an atherosclerotic mouse model. Aortic tissue from wild type and apolipoprotein E-deficient mice, both fed a high-fat diet, were stained with either fluorescent-labeled gAd or gAd-coupled nanoparticles. Ex vivo imaging was performed using confocal laser scanning microscopy.Results: gAd-targeted sterically stabilized liposomes generated a strong signal by accumulating at the surface of atherosclerotic plaques, while gAd-targeted proticles became internalized and showed more spotted plaque staining.Conclusion: Our results offer a promising perspective for enhanced in vivo imaging using gAd-targeted nanoparticles. By means of nanoparticles, a higher payload of signal emitting molecules could be transported to atherosclerotic plaques. Additionally, the opportunity is opened up to visualize different regions in the plaque scenario, depending on the nature of the nanoparticle used.Keywords: adiponectin, nanoparticles, proticles, liposomes, molecular imaging, atherosclerosis